Pengaruh Pemberian Pupuk Kandang Kelinci Dan Poc Batang Pisang Terhadap Pertumbuhan Dan Produksi Kacang Hijau (Vigna Radiata L.) - Hardi Rachman; Wan Arfiani Barus; Rini Susanti (GEMA AGRO, 2021)
This research was conducted from January to April 2019 on Jl. Sampali Meteorology in Percut Subdistrict, North Sumatra Province with Altitude + 27 m above sea level. This study aims to determine the effect of the application of rabbit manure and Liquid Organic Fertilizer (LOF) banana stem to the growth and production of green beans. This study used Factorial Randomized Block Design with 2 factors, the first factor was Banana Liquid Organic Ferlizer (LOF ) with 3 levels: P1 (300 ml / l), P2 (450 ml / l) and P3 (600 ml / l) and the second factor giving Rabbit Cage Fertilizer with 4 levels, namely K0 (control), K1 (1 Kg / Plot) and K2 (2 Kg / Plot) And K3 (3 Kg / Plot) The parameters measured were plant height, number of primary branches, flowering age, number of pods containing sample plants, number of empty pods for sample planting, weight of planting seeds, weight of 100 seeds, leaf area. Data from the observations were analyzed using analysis of variance (ANOVA) and continued with a mean difference test according to the Duncan Multiple Range Test (DMRT). The results showed that the liquid organic fertilizer of banana stems had no effect on all parameters of green bean plants. Fertilizer for rabbit manure significantly affected the number of branches and age of green bean plants with K3 (3 Kg / Plot) treatment. There was no interaction between liquid organic fertilizer and rabbit droppings on all parameters